Expressive Tendencies of Language in the World of Print Media - Safarmakhmatova Zarrina Narzulloevna (European Science Publishing, 2023)
The media image of the world is a product of a person's continuous informational activity, the continuous objectification of mental activity in knowing the world, the constant externalization of the mind of many people and the worldview or image of the world by the mind of individual people through actualization in mass media texts.
Keywords: expressiveness, category, field, explanation, approach